Public sector accounting - Jones, Rowan; Pendlebury, M. (London : Pearson, 2010)
This book provides a comprehensive examination of the special issues concerning accounting in the public sector of the economy, discussing why public sector accounting is different from accounting for business organisations.
Includes index (p. 141-146).
1 The nature of the public sector 2. Performance measurement 3. Fundamentals of accounting 4. Budgetary policies and processes 5. Form and contents of budgets 6. Budgetary control 7. Costing 8. Financial reporting
Keywords: Budgetary control; Financial reporting; Auditing